Research trends on lactate in cancer: a bibliometric analysis and comprehensive review (2015–2024) - Li, Sinong; Yang, Ziyi; Lv, Mutian; Zong, Lin; Xie, Yihan; Cai, Zoujuan; Zhang, Ying; Wang, Zhongqing; Liu, Zhe; Sang, Liang (Frontiers in Immunology, 2025)
ObjectiveA bibliometric approach was employed to systematically analyze the trends and potential future developments in lactic acid-related cancer research over the past 10 years.MethodWe conducted a bibliometric analysis of literature on lactic acid in cancer research from 2015 to 2024, using data collected from the Web of Science database. A bibliometric analysis was conducted to identify general research directions and trends in current publications, as well as to determine the most prolific and influential authors, institutions, countries, and keywords in lactate and cancer research. The data were collected and analyzed using VOSviewer (Leiden University, Leiden, Netherlands), Microsoft Excel (Microsoft, Redmond, Washington, USA), CiteSpace, and Biblioshiny, with a focus on analysis and visualization.ResultsA total of 5,999 publications were analyzed, focusing on various aspects of the relevant literature, including year of publication, country, institution, author, journal, category, keywords, and research frontiers. The analysis of these publications reveals a general upward trend in publication volume from 2015 to 2024, with China and University of California System emerging as the most prolific country and institution, respectively. SCIENTIFIC REPORTS is the most frequently published journal, while Oncotarget is the most cited journal in the field. Zhang Y. was the most prolific author, publishing 100 documents over 10 years, with the highest citation count and an H-index of 28.Keyword analysis revealed five key themes in lactate-cancer research (2013–2023): Metabolic-epigenetic crosstalk, Tumor immunosuppressive microenvironment, Innovative therapies/drug delivery, Lactate-mediated signaling, Metabolic-targeted treatment strategies. Current research emphasizes the application of lactic acid metabolism in metabolic intervention, immune microenvironment regulation, combination of new therapeutic techniques and applications in specific cancer types.ConclusionResearch on lactic acid in cancer is growing rapidly, with China at the forefront of this field. Research into lactic acid’s role in immune cell regulation, metabolism, and signaling pathways, combined with multi-modal imaging, big data analytics, and innovative drug delivery, is set to become a key trend in future studies, which promises new directions for identifying therapeutic targets, biomarkers, and developing advanced treatments.